2016
DOI: 10.1002/acr.22668
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment for Rapid Improvement of Both Disease Activity and Self‐Reported Physical Activity in Early Rheumatoid Arthritis

Abstract: Objective. To investigate the longitudinal relationship between disease activity and self-reported physical activity (PA) in patients with early rheumatoid arthritis during the first year of treatment with combination therapy. Methods. PA was measured with the Short Questionnaire to Assess Health-Enhancing Physical Activity at baseline, 13 weeks, 26 weeks, and 52 weeks after start of treatment in the context of the Combinatietherapie Bij Reumato€ ıde Artritis-Light trial. The reported PA classified patients as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
9
1
3
Order By: Relevance
“…It is therefore not surprising that people with RA have indicated that once their disease activity is controlled, they are more likely to engage with behavioural interventions to reduce CVD risk, such as exercise [36][37][38]. Observational studies show that following successful treatment of disease activity in RA self-reported physical activity was increased [39] and medication-induced improvements in disease activity were related to physical activity increases [40]. Thus, providing support by offering exercise programmes when the disease is controlled, is likely to enhance the uptake and the maintenance of exercise, which as the current study reveals will result in additional benefits to their CVD risk and vascular function, as well as functional ability and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore not surprising that people with RA have indicated that once their disease activity is controlled, they are more likely to engage with behavioural interventions to reduce CVD risk, such as exercise [36][37][38]. Observational studies show that following successful treatment of disease activity in RA self-reported physical activity was increased [39] and medication-induced improvements in disease activity were related to physical activity increases [40]. Thus, providing support by offering exercise programmes when the disease is controlled, is likely to enhance the uptake and the maintenance of exercise, which as the current study reveals will result in additional benefits to their CVD risk and vascular function, as well as functional ability and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both disease-related factors and CVD risk factors have been shown to contribute to CVD events in RA [7], the combination of exercise and anti-TNF treatment might provide the best protection for CVD in RA. Pain, fatigue and functional ability are commonly mentioned barriers to exercise and physical activity [27], and observational studies already showed increases in physical activity following successful treatment of disease activity [39,40]. Thus, supporting exercise programmes for people with RA when the disease is controlled, is likely to enhance the uptake and the maintenance of exercise, which will result in additional benefits for cardiovascular health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation might be that a low level of disease activity with fewer symptoms in the patients included in this study contributed to increased opportunities for these patients to be physically active. Research shows that there is a relationship between physical activity and disease activity, and patients with a low level of disease activity tend to be more physically active 3840. Furthermore, it is also important to be aware of patients’ beliefs about the positive effect of physical activity in reducing their symptoms,41 and it has been found in several qualitative studies that patients emphasize the importance of physical activity in the management of their CIA and as a way of maintaining control over their symptoms and their lives and of being independent 42,43.…”
Section: Discussionmentioning
confidence: 99%
“…A AR requer acompanhamento sistemático, avaliação da capacidade funcional e prática regular de atividade física (9)(10)(11)(12)(13)(14)(15)(16) . O Consenso Brasileiro do tratamento de Artrite Reumatóide de 2012, recomenda visitas de monitoramento mensais àqueles que estão no início da doença e aos que estão com a doença estabilizada, a cada três meses, o que se assemelha muito à intervenção de enfermagem oferecida no presente estudo (5) .…”
Section: Repenunclassified
“…A prática de atividade física é altamente recomendada pelos benefícios proporcionados no âmbito físico, psicológico e social (13)(14) . Além disso, pode minimizar o avanço da doença (13)(14)(15) , o risco para doenças cardiovasculares e a ocorrência de fraturas (15)(16) , o que consequentemente promove a melhora na funcionalidade desses indivíduos .…”
Section: Introductionunclassified